System approach to energy saving potential estimation on the сertain countries and regions level - N. A. Kislenko; Y. S. Kopylova; N. V. Malanicheva (Вестник университета)
The energy saving potential is related directly to the increase of gas application efficiency. Herewith, energy use efficiency is a complex concept, including not only the issues of technological efficiency, but also the requirements for the economic, social and environmental components of the processes. Meanwhile, the problem of energy efficiency assessment is a more general problem of effective use of resources in comparison with alternative energy and resource-using processes, reduced to comparable analysis conditions. In addition, efficiency should be distinguished from the point of view of consumers, producers and suppliers of energy resources, as well as from the point of view of general economic (state) efficiency.